Increased summer food supply decreases non-breeding movement in black-legged kittiwakes. (29th January 2020) - Whelan, Shannon; Hatch, Scott A.; Irons, David B.; McKnight, Alyson; Elliott, Kyle H.
Abstract : Individual condition at one stage of the annual cycle is expected to influence behaviour during subsequent stages, yet experimental evidence of food-mediated carry-over effects is scarce. We used a food supplementation experiment to test the effects of food supply during the breeding season on migration phenology and non-breeding behaviour. We provided an unlimited supply of fish to black-legged kittiwakes ( Rissa tridactyla ) during their breeding season on Middleton Island, Alaska, monitored reproductive phenology and breeding success, and used light-level geolocation to observe non-breeding behaviour. Among successful breeders, fed kittiwakes departed the colony earlier than unfed controls. Fed kittiwakes travelled less than controls during the breeding season, contracting their non-breeding range. Our results demonstrate that food supply during the breeding season affects non-breeding phenology, movement and distribution, providing a potential behavioural mechanism underlying observed survival costs of reproduction.